Brazo robótico controlado por un control Joystick de forma inalámbrica, montado sobre una base móvil. - Caraguay Jaén, Jorge Enrique (2011)
In 1920, the Czechoslovakian writer Karel Capek wrote his play. The universal robots of Rossum (RUR Universal Robots) with which, surely without intending it, added a new word to the vocabulary: robot. The staging of the premiere in Prague, a year later, faithfully followed the theme of the work: the exploration of the loss of the identity of man in a civilization based on technology. The word robot is not accidental in that context; Comes from the Czech word robota, which has connotations of routine, forced or difficult work. In 1941, another writer, the famous Isaac Asimov, emphasized the robotic expression to designate the technology applied in the robots. Once again, fiction anticipated science. Only in 1956 was the first robot company founded (created by George Devol and Joseph Engel Berger) and in 1961, General Motors assembled the world's first industrial robot in its New Jersey factory. Two years later another breakthrough was created: the Arm Ranch, the first arm controlled by a computer. And, in 1970, the Shakey was the first mobile robot commanded by artificial intelligence. The professional field of the electronic technologist requires, acquisition of theoretical-practical studies that involve a scientific-technical action. Faced with the lack of knowledge of robotic technology that contrasts with the need for theoretical and practical understanding of this subject, this project provides us with significant learning of the technical characteristics, functioning of those elements that make up the movement, control, sensitivity and The application of the programmable logic required by the systems in which we are going to work. The theoretical foundations corresponding to the learning of the operation of components of analog electronics and digital electronics have allowed us to have the capacity to carry out this project, however a research of the science of robotics is necessary because it is a branch of computer science with a Wide difference in main subjects such as the different types of programmable logic software and artificial intelligence. The use of components such as transistors, integrated circuits, microcontrollers (PICS), sensors; Which within the electronic technology have been studied and also of the new elements that will be presented due to the robotics; Will support the implementation of the project. With this research we seek the application of the knowledge acquired to determine the stability of the system and the sensitivity it has to variations in movement. We will also try to know the applications of this project in society with respect to the different industrial sectors, transportation, which use the use of machines to transport objects from one place to another. This circuit is powered by a direct current source, which makes it suitable for use even in power suspensions in the electric service network, as it can work with the use of batteries. This is possible thanks to the low overall consumption of the appliance. This research project provides a source of knowledge and construction on similar topics for those who are going to investigate this document. In this way we propose the following objectives: General:  Build a robotic arm controlled by a wireless joystick control, mounted on a mobile base. Specific:  Build a robotic instrument that provides a practical understanding of the knowledge of some technical characteristics of robotic systems, where control and motion functions will be applied.  Apply automation, telecommunications and microcontroller programming as branches of electronics.